Generalized Joint Hyper Mobility is not Associated with the Development of Overuse Arm Injuries in Adolescent Baseball Pitchers. Issue 7 (21st July 2017) - Tokish, John M.; Shanley, Ellen; Bailey, Lane Brooks; Kissenberth, Michael J.; Sease, Wayne F.; Hawkins, Richard J.; Thigpen, Charles A.
Objectives: Generalized joint hypermobility is theorized as a risk factor for joint injury in sport. However, there are no studies demonstrating generalized joint hypermobility and upper extremity overuse injury. Therefore the purpose of this study was to prospectively examine generalized joint hypermobility using the Beighton Scale and upper extremity overuse injuries in high school baseball pitchers. Methods: Healthy high school baseball pitchers (n=167) who were participating in all team activities were included in the study. The players averaged 15.8 ± 1.2 y.o., weighed 72.3 ± 13.0 kg, and measured 165.0 ± 43.8 cm in height. They were assessed during the preseason for joint hypermobility using the 9-point Beighton scale. From the first official day of practice until the last regular or postseason competition, all athletes who reported pain or injury to their coach were referred to the certified athletic trainer (AT) at their school for evaluation and classification of each potential injury. Verified overuse injuries were tracked and documented in the Athletic Trainer System (ATS) by the schools AT. The ATS system was also used to identify players with a history of upper extremity injuries. Generalized joint hypermobility was defined as modified Beighton scale scores ≥ 4. Separate one-way ANOVA's were used to determine the mean Beighton scores between groups. A chi square analysis was used to assess the frequency of overuse injuries in those with a Beighton score of ≥ 4 and those with elbow hyperlaxity. (α=0.05) Results: The prevalence of generalized hypermobility in this cohort was 35.3%. Of those pitchers sustaining a time-loss overuse injury (n=23), only 4 presented with a Beighton score ≤ 4. The average Beighton score in those sustaining a time-loss overuse injury was similar to the Beighton score of those pitchers remaining healthy (2.9 ± 2.1 vs. 2.5 ± 2.1; P =0.59), respectively. There was no difference in the Beighton score of pitchers with a history previous injury when compared to pitchers without a history of injury (2.7 ± 2.1 vs. 2.6 ± 2.0; p=0.75), respectively. Injured pitchers with a Beighton score ≥ 4 presented with similar time-loss as pitchers with a lower Beighton score ( P = 0.93). The relative risk of injury for a pitcher with a Beighton score ≥ 4 was similar to pitchers with a lower Beighton score (RR= 1.0, 95% CI: .54-1.8). Hyperlaxity at the elbow was not associated with elbow overuse injury ( P =0.29). Conclusion: Generalized joint hypermobility, as defined by a Beighton score ≥ 4 or elbow hyperlaxity, did not increase the risk of developing an upper extremity overuse injury in this cohort of adolescent baseball pitchers. Additionally, injured pitchers with higher Beighton scores returned to participation within a similar timeframe as those with less generalized joint hypermobility.